2015
DOI: 10.3766/jaaa.14089
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Oculomotor Findings during Monocular Videonystagmography: A Developmental Study

Abstract: Significant differences were noted between the pediatric and adult participants for saccade latency, smooth pursuit gain, and OPK asymmetry. Saccade latency was significantly longer for the pediatric participants compared to the adult participants. Smooth pursuit gain was significantly less for the pediatric participants compared to the adult participants. The pediatric participants also demonstrated increased OPK asymmetry compared to the adult participants. Caution should be exercised when comparing pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
(40 reference statements)
1
12
0
2
Order By: Relevance
“…Standard error bars are noted. 17 greater for the pediatric participants than adult participants. Development of the vestibular nuclei, nucleus of the optic track, accessory optic system, cerebral cortex, parietal lobes, and temporal lobes are related to OPK function, specifically decreased variability, with an increase in age.…”
Section: Saccade Testingmentioning
confidence: 86%
See 1 more Smart Citation
“…Standard error bars are noted. 17 greater for the pediatric participants than adult participants. Development of the vestibular nuclei, nucleus of the optic track, accessory optic system, cerebral cortex, parietal lobes, and temporal lobes are related to OPK function, specifically decreased variability, with an increase in age.…”
Section: Saccade Testingmentioning
confidence: 86%
“…[8][9][10][11][12][13][14][15][16] These documented age effects pose several questions with regard to the clinical vestibular evaluation of oculomotor function in children. To answer these questions, Doettl et al 17 completed oculomotor testing using videonystagmography (VNG) consisting of saccades and smooth pursuit, and OPK using standard clinical equipment and protocols in pediatric and adult populations to investigate for age affects with regard to saccade latency, accuracy, speed, smooth pursuit gain, OPK nystagmus gain, speed, and asymmetry ratio.…”
Section: Age Effects In Pediatric Oculomotor Assessmentmentioning
confidence: 99%
“…Among the oculomotor tests, saccade maintains the position of an image of a target over the fovea in the case of quick eye movement (10). Saccade functions, especially latency and velocity, improve with age via development of the prefrontal function and brain myelination, visual maturation and development of the cerebral cortex (9). Saccade can be impaired in cases of intoxication such as anticonvulsive or benzodiazepine use and in neurodegenerative disorders such as brainstem lesions, midbrain lesion, progressive supranuclear palsy, cerebellum or cerebellar pathways (17 peripheral vestibular disorder and claimed that vestibulo oculomotor dysfunction may be a sign of peripheral dysfunction as well as central nervous system impairment (10).…”
Section: Smooth Pursuitmentioning
confidence: 99%
“…Optokinetic nystagmus occurs rhythmically, involuntarily, unconsciously and automatically (10). Optokinetic function is related to vestibular nuclei, nucleus of the optic track, accessory optic system, cerebral cortex, temporal lobes, and parietal lobes (9). Tuma et al demonstrated that optokinetic nystagmus gain was altered in 5.0% of patients with…”
Section: Disclosurementioning
confidence: 99%
See 1 more Smart Citation